Psalm 2 as lied teks – ‘n literêre en teologiese evaluering - Vos, Casparus Johannes Adam (Verbum et ecclesia, 2004)
The publishing of the Liedboek (2001) emphasizes the importance of the psalms for liturgy and hymnology. All 150 psalms in the Liedboek were versified by T T Cloete. In this article Psalm 2 is analysed from different perspectives. This leads to a literary and theological evaluation of its versification by Cloete.